PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP MINAT BELI KONSUMEN DI NUSANTARA MART GENDINGAN TULUNGAGUNG - Kevin Ganardi (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to identify and explain about the influence of service quality, product quality, price and promotion on consumer buying interest in Nusantara Mart Tulungagung. This research is a descriptive study with quantitative methods, the sampling technique used is saturated sampling technique, with a total population and sample of 110 respondents or consumers. The analysis technique used is validity test, test reliability, multiple linear regression analysis, t test (partial) and F test (simultaneous) test the coefficient of determination (R2) which was processed using the SPSS (Statiscal Product and Service Solution) program. The results of the study concluded that partially there is a positive and significant influence between service quality, product quality, price and promotion on consumer buying interest at Nusantara Mart Tulungagung. Service quality partially has a positive and significant influence on consumer buying interest, this can be seen from the significant value of t of 0.033 > 0.05. Product quality partially has a positive and significant effect on consumer buying interest, this can be seen from the significant value of t of 0.003> 0.05. Price partially has a positive and significant effect on consumer buying interest, this can be seen from the significant value of t of 0.028 > 0.05. Promotion partially has a positive and significant effect on consumer buying interest, this can be seen from the significant value of t of 0.068 >0.05. Service quality, product quality, price and promotion simultaneously have a positive and significant effect on consumer buying interest in Nusantara Mart Tulungagung, this is from a significant value of F of 0.000 <0.05.